The Unfavourable Split: a novel classification and an 11-year retrospective study looking at alternative methods for management of this well-known complication. Issue 1 (January 2023) - Chandegra, Rohit Kumar; Tsakalidis, Michail; Pandya, Rishi; Stockton, Peter
Abstract: An unfavourable split is a well-known complication following a sagittal split osteotomy (SSO) of the mandible. Our aim was to analyse all unfavourable mandibular splits that had occurred when carrying out a SSO with the aim to design a classification which can facilitate management. We carried out a retrospective study analysing all orthognathic surgery from January 2010 until April 2021. Data surrounding unfavourable splits during this period were specifically analysed. Orthognathic surgery during this period was performed by a single OMFS unit with osteotomies performed by a single surgeon and their trainee. The dataset included 311 patients who underwent either a bilateral sagittal split osteotomy (BSSO) or a bimaxillary osteotomy. There were 225 bimaxillary osteotomies and 86 BSSOs. Twenty-one patients had unfavourable splits following their BSSO with a total of 22 out of 622 sagittal split osteotomies over this 11-year period. Bilateral unfavourable splits occurred in one patient. These results correlate to an incidence rate of 6.8% of unfavourable splits following SSO's in an 11-year period. The results reveal common patterns of unfavourable splits to suggest a simple classification based on our results. This can be applied to any unfavourable splits in SSO which then allows the clinician to proceed with surgery and prevent abandonment of the procedure. It is classified as follows: Type 1 fractures where the mandibular condyle is attached to the proximal fragment; Type 2 fractures whereby the mandibular condyle is attached to the tooth-bearing segment; Type 3 fractures are lingual cortex fractures. Each of these fracture types has a specific management protocol, which we recommend is used in all unfavourable splits.